Risk factors for the incidence of dengue in the Alhajuela community in Ecuador - Ivicevic, Zdravko; Rodríguez, Edgar E.; Moreira, Winther B.; Constante, Claudia V.; Dueñas, Andrea V.; Vinces, Frank S.; Párraga, José H. (Revista Gregoriana de Ciencias de la Salud, 2025)
This study analyzed the risk factors associated with dengue incidence in Alhajuela Parish, Manabí, Ecuador, to inform prevention strategies tailored to the local context. A structured survey was administered to 41 residents aged 18 years or older, gathering data on dengue knowledge, Aedes aegypti breeding sites, hygiene habits, and protective measures. Results showed that 41.5% of participants lacked basic knowledge about the disease, and 61% reported breeding sites near their homes. Only 34.1% of water containers were cleaned daily, while mosquito nets (95.1%) and repellents (53.6%) were the most common preventive methods. A clear association was found between poor domestic hygiene and higher exposure to the vector. The convergence of environmental factors, poor sanitation infrastructure, and limited community education increases the risk of dengue transmission. The study concludes that it is essential to strengthen educational campaigns, improve basic services, and promote community participation to reduce the incidence of this disease.